Garis Panduan Sertu Menurut Perspektif Islam-Jakim: A Critical Review - Wan Ainaa Mardhiah Wan Zahari; Nur Zainatul Nadra Zainol; Mohd Mahyeddin Mohd Salleh; Mohd Nasir Abdul Majid; Irwan Mohd Subri; Ahmad Sharifuddin Mustapha (USIM Press, 2026)
Indexed by Scopus